Prevalence of diarrheal disease and associated factors among under-five children in flood-prone settlements of Northwest Ethiopia: A cross-sectional community-based study - Tsegaye Adane Birhan; Bikes Destaw Bitew; Henok Dagne; Dagnachew Eyachew Amare; Jember Azanaw; Mengesha Genet; Garedew Tadege Engdaw; Amensisa Hailu Tesfaye; Getasew Yirdaw; Tadele Maru (Frontiers Media S.A., 2023)
BackgroundDiarrheal illnesses are a long-standing public health problem in developing countries due to numerous sanitation issues and a lack of safe drinking water. Floods exacerbate public health issues by spreading water-borne infectious diseases such as diarrhea through the destruction of sanitation facilities and contamination of drinking water. There has been a shortage of studies regarding the magnitude of diarrheal disease in flood-prone areas. Therefore, this research aimed to evaluate the prevalence of diarrheal disease and its predictors among under-five children living in flood-prone localities in the south Gondar zone of Northwest Ethiopia.MethodA community-based cross-sectional research was carried out in flood-prone villages of the Fogera and Libokemkem districts from March 17 to March 30, 2021. Purposive and systematic sampling techniques were used to select six kebeles and 717 study units, respectively. Structured and pretested questionnaires were used to collect the data. A multivariable analysis was performed to determine the predictors of diarrheal disease, with P-value <0.05 used as the cut-off point to declare the association.ResultThe prevalence of a diarrheal disease among under-five children was 29.0%. The regular cleaning of the compound [AOR: 2.13; 95% CI (1.25, 3.62)], source of drinking water [AOR: 2.36; 95% CI: (1.26, 4.41)], animal access to water storage site [AOR: 3.04; 95% CI: (1.76, 5.24)], vector around food storage sites [AOR: 9.13; 95% CI: (4.06, 20.52)], use of leftover food [AOR: 4.31; 95% CI: (2.64, 7.04)], and fecal contamination of water [AOR: 12.56; 95% CI: (6.83, 23.20)] remained to have a significant association with diarrheal diseases.ConclusionThe present study found that the prevalence of the diarrheal disease among under-five children was high. Routine compound cleaning, the source of drinking water, animal access to a water storage site, vectors near food storage sites, consumption of leftover food, and fecal contamination of water were significant predictors of diarrheal disease. Therefore, it is advised to provide improved water sources, encourage routine cleaning of the living area, and offer health education about water, hygiene, and sanitation.